Exploring a New Tourism Potential at Kampung Telok Melano, Sarawak Malaysia Post PanBorneo Highway Construction - Dilah, Tuah; Chong, Shin; Muhammad Jazlan, Ahmad Khiri (Human Resource Management Academic Research Society, 2022)
Sarawak's economic sector relies on tourism as a stimulant. This research evaluated the potential of a new tourist destination in Sarawak, particularly in a region involved in the construction of the Pan-Borneo highway. The research was carried out as a pioneering research focus at Kampung Telok Melano, Sematan, which is the starting point for the PanBorneo highway project in Sarawak's southwest. The selection of Kampung Telok Melano as the study's location is notable since this region has been featured in a tourist program (homestay) since 1996, governed by Malaysia's Fisheries Development Authority. However, due to a lack of adequate road access as well as basic amenities, Kampung Telok Melano only attracts a small number of visitors from both within and outside the nation. As a result, the impact of the Sematan-Telok Melano Pan-Borneo highway on the local population was examined in this study. This is a qualitative study that incorporated both library and field research. This research extensively reviewed and discussed all the data acquired through recorded conversations, interviews, and observations. According to the findings, Kampung Telok Melano has the potential to become a major tourist destination in Sarawak once the Pan-Borneo highway is completed. This research also revealed that the development of the Pan-Borneo highway improved infrastructure, raised living standards, and offered a source of income for its inhabitants. A quantitative study for additional research must be conducted in the near future to find the actual impact of the Pan-Borneo highway project on Sarawak's tourist sector and local population.